Studi Pelapisan Krom Pada Baja Karbon Dengan Variasi Waktu Pencelupan 10, 20, 30, 40, 50 Menit Dan Tegangan 9 Volt Dengan Arus 5 Ampere - , Suharto, Agus Dwi Anggono, ST.M.eng. PhD (2017)
The purpose of this study was to investigate the effect of chromo coating process parameters ie the time of immersion on microstructure and surface hardness of the product. The experiment was conducted by experimental method using carbon steel electrode, chromium electrolyte solution, additive, direct current source, and other plating equipment. The microstructure of chromium products was observed to analyze coating thickness. Evaluation of the mechanics is done to measure the hardness. The results of this study will increase the knowledge for chrome industry players to improve product quality both for corrosion protection, increased wear resistance, and to increase the decorative value of its products.